2020
DOI: 10.1186/s12889-020-09266-4
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of caregiver burden of persons with disabilities in a rural district in Egypt

Abstract: Background: Family caregivers are critical partners in the plan of care of people with disabilities. The study aims to demonstrate the factor structure and internal consistency of the Caregiver Burden Inventory (CBI) among the studied caregivers of disabled persons and to determine the effects of patients' and caregivers' characteristics on the burden and its dimensions. Methods: A cross-sectional study among 260 family caregivers of disabled patients was carried out in a randomly chosen rural area, Minia, Egy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 33 publications
1
8
0
3
Order By: Relevance
“…Due to juggling caregiving responsibilities and work, the caregivers reported they could not meet their objectives due to fatigue and spending most time away, especially due to frequent medical check-ups needed by their children. The findings are supported byFast (2015) in a study that revealed working caregivers have decreased productivity at their jobs especially public sector employees. They miss most days at work due to their caregiving responsibilities, which consequently affects their productivity negatively and posing a risk of getting fired.…”
supporting
confidence: 55%
See 1 more Smart Citation
“…Due to juggling caregiving responsibilities and work, the caregivers reported they could not meet their objectives due to fatigue and spending most time away, especially due to frequent medical check-ups needed by their children. The findings are supported byFast (2015) in a study that revealed working caregivers have decreased productivity at their jobs especially public sector employees. They miss most days at work due to their caregiving responsibilities, which consequently affects their productivity negatively and posing a risk of getting fired.…”
supporting
confidence: 55%
“…According to Ghazawy et al ( 2020 ), as the strain of caring for a child living with a disability increases, caregivers can face exposure to mental and physical health difficulties, which may affect their quality of life if they cannot receive support. In this study, the participants described the overall health of the caregiver as one of the challenges they experience as they care for their children living with disabilities.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, all of the stroke survivors in our study had high levels of dependence, most were older adults, and more than two-thirds had other chronic illnesses—factors that also determine the care burden 26 54 82–87. These findings reflect the social conditions of Egyptian family caregivers and the growing care demands of stroke survivors that are inherent to the concept of care burden and other negative stressors 32 88 89…”
Section: Discussionmentioning
confidence: 63%
“…In this way, family members need to mobilize all available resources to face critical economic conditions, seeking, for example, to produce food and raise animals for consumption. Thus, a cross-sectional study carried out in a rural area of Egypt, with 260 family caregivers of DP, revealed that 37% (n = 90) reported worsening in their economic level ( 38 ) . Financial difficulties prevent, among others, the purchase of medicines and the use of transport to seek health care ( 13 - 14 , 31 ) .…”
Section: Discussionmentioning
confidence: 99%